Effects of canagliflozin on hyperkalaemia and serum potassium in people with diabetes and chronic kidney disease: insights from the CREDENCE trial. (14th October 2021) - Neuen, B L; Oshima, M; Perkovic, V; Arnott, C; Bakris, G; Cannon, C P; Charytan, D M; Jardine, M; Levin, A; Neal, B; Pollock, C; Wheeler, D C; et al.
Abstract: Background: Hyperkalaemia is a common complication of type 2 diabetes mellitus (T2DM) and limits the optimal use of agents that block the renin-angiotensin aldosterone system (RAAS), particularly in patients with chronic kidney disease (CKD). In patients with CKD, sodium glucose cotransporter 2 (SGLT2) inhibitors provide cardiorenal protection, but whether they affect the risk of hyperkalaemia remains uncertain. Purpose: We sought to assess the effect of canagliflozin on hyperkalaemia and other potassium-related outcomes in people with T2DM and CKD by conducting a post-hoc analysis of the CREDENCE trial. Methods: The CREDENCE trial randomized 4401 participants with T2DM and CKD to the SGLT2 inhibitor canagliflozin or matching placebo. In this post-hoc analysis using an intention-to-treat approach, we assessed the effect of canagliflozin on a composite outcome of time to either investigator-reported hyperkalaemia or the initiation of potassium binders. We also analysed effects on central laboratory-determined hyper- and hypokalaemia (serum potassium ≥6.0 and <3.5 mmol/L, respectively) and change in serum potassium. Results: At baseline the mean serum potassium in canagliflozin and placebo arms was 4.5 mmol/L; 4395 (99.9%) participants were receiving renin angiotensin system blockade. Canagliflozin reduced the risk of investigator-reported hyperkalaemia or initiation of potassium binders (HR 0.78, 95% CI 0.64–0.95, p=0.014; Figure 1). The incidence of laboratory-determined hyperkalaemia was similarly reduced (HR 0.77, 95% CI 0.61–0.98, p=0.031; Figure 2); the risk of hypokalaemia (HR 0.92, 95% CI 0.71–1.20, p=0.53) was not increased. Mean serum potassium over time with canagliflozin was similar to that of placebo. Conclusion: Among patients treated with RAAS inhibitors, SGLT2 inhibition with canagliflozin may reduce the risk of hyperkalaemia in people with T2DM and CKD without increasing the risk of hypokalaemia. FUNDunding Acknowledgement: Type of funding sources: None.